2019
DOI: 10.14807/ijmp.v10i6.967
|View full text |Cite
|
Sign up to set email alerts
|

Nias-mukalla web based systems success measurement and students satisfaction evaluation based on security factor of systems quality engineering theory (ISO 25010) and other factors

Abstract: Latest studies reported that systems success measure suffers from mix of results and limited models that help in success measurement and evaluation.Because of systems models are domain specific and context related, there is a dire need for taking the measure to other perspectives like using related external factors such as management support or using software engineering theories such as ISO 25010. This study aimed to move the measure from a business perspective to other perspectives.This study investigated NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There is a dire need for a strong validated instrument for systems success measurement, especially in the least developed countries. The goal behind this study is to provide a strong validated instrument for systems quality measurement and success evaluation [3,4,6,[16][17][18] .…”
Section: Problem Statementmentioning
confidence: 99%
“…There is a dire need for a strong validated instrument for systems success measurement, especially in the least developed countries. The goal behind this study is to provide a strong validated instrument for systems quality measurement and success evaluation [3,4,6,[16][17][18] .…”
Section: Problem Statementmentioning
confidence: 99%
“…According to Iivari [67], computer-aided software for technology helps to enhance the functionality of the system and its compatibility. Fadhel et al [68] found that their developed system met the needs of users and further facilitated use. According to Rodger [69], a developed system can maintain the safety of the user, which can reduce the accidents caused by the inefficiency of the user.…”
Section: Quality Of Technology Systemmentioning
confidence: 99%